Antecedents of Islamic Organizational Citizenship Behavior Toward Job Performance - Mubarok, Muhammad Husni; Martini, Tina (EQUILIBRIUM, 2021)
This study aims to investigate the development model and explore the relationship between Islamic organizational citizenship behavior based on organizational identification, person-organization fit, and job satisfaction towards job performance in Islamic finance in Indonesia. Specifically, this study argues that Islamic organizational citizenship behavior moderates the relationship between organizational identification, person-organization fit, and job satisfaction with job performance. Employees of Islamic finance in Indonesia were selected as the main targets of this study. Two hundred ninety questionnaires were distributed among employees of Islamic finance in Indonesia. Two hundred forty-six valid responses was received (response rate is 84.8%). After analyzing data from 246 employees of Islamic finance in Indonesia, empirical testing shows that the personorganization fit influences the Islamic organizational citizenship behavior and has a strong correlation. However, organizational identification and job satisfaction do not affect Islamic organizational citizenship behavior. The main finding of this study is that Islamic organizational citizenship behavior has a positive relationship with the job performance of Islamic finance in Indonesia.